Cognitive Function and Blood Pressure Examination in Padang Bulan Selayang II Subdistrict - Nasution, Irina Kemala; Rambe, Aldy Safruddin; Fitri, Fasihah Irfani; Iswandi Erwin (Talenta Publisher Universitas Sumatera Utara, 2018)
Hypertension is one of the main health problems in Indonesia, which if not controlled will result in health, psychological, social and economic burdens. A common clinical consequence of hypertension is impaired cognitive function, namely dementia and senility, which can be examined through the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina). The service program which is carried out by the Faculty of Medicine, Universitas Sumatera Utara (FK USU) is an examination of cognitive function and blood pressure in Padang Bulan Selayang II region. Examinations are carried out in accordance with the 2017 World Alzheimer Month and are followed by lay seminars on dementia, brain gym exercises (gerak latih otak/GLO) as well as brain teasers. The activity involved 26 participants from integrated development post (pos pembinaan terpadu/Posbindu) with a mean systolic blood pressure (TDS) 131.54 + 18.70 mmHg, mean diastolic blood pressure (TDD) 83.85 + 8.98 mmHg, mean mean arterial pressure 99, 69 + 9.47 mmHg and a mean MoCA-Ina score of22 + 5.03. Blood pressure monitoring, education of community awareness and cognitive stimulation at regular intervals are expected to prevent and reduce the incidence of hypertension, dementia and senility.